Comparison of Periphyton Biomass on Coconut Coir and Bamboo Poles as Natural Substrates in Earthen Lined Pond - Anix, A.; Santhiya, Vivek; Athithan, S.; Ahilan, B. (International Journal of Bio-resource and Stress Management, 2020)
As a first step in assessing the viability of periphyton-based shrimp production in lined pond aquaculture systems, the effects of natural substrates (split bamboo poles and coconut coir) on development of periphyton were evaluated. Experiments were conducted in outdoor earthen lined pond to study periphyton biomass on two types of natural substrates such as split bamboo pole and coconut coir which was placed inside the earthen lined pond filled with seawater for duration of 45 days. The periphyton biomass was recorded at 0–40 cm depth, 40–80 cm depth and 80–120 cm for all the substrates. The periphyton biomass, in terms of dry matter (DM) from coconut coir was comparatively higher (3.4995±0.3120 mg cm-2) than the split bamboo poles (3.2011±0.3044 mg cm-2) during the experiment. ‘T’ test has affirmed that significant difference (p<0.05) was observed in the dry matter content of the periphyton among the substrates. ‘T’ test analysis of the data relating to periphyton biomass for split bamboo pole and coconut coir recorded at different depths indicated that upper 0–40 cm depth had higher values than the other depths. Furthermore, among the two substrates, coconut coir (3.4995 ± 0.31201 mg cm-2) was observed to be a better substrate than the split bamboo pole for periphyton biomass production. Coconut coir substrate can be utilised by fin and shellfishes as natural food.